Urban Characterization by the Green Supply Chain Management Concept: A Review - Hany Hossam Eldien; Karim Gazzeh; Emad Hammad (International Journal of Supply Chain Management, 2020)
Abstract- In a review of the supply chain management of an urban area was examined in an imperative to demonstrate the benefits of a supply chain management method for an urban designing. Supply chains provide the critical infrastructure for the production and distribution of goods and services in our network economy and serve as the conduits for the manufacturing, transportation, and consumption of products ranging from food, clothing, automobiles, and high-technology products, to healthcare products. Cities as major population centers serve not only as the principal demand points but also as the locations of many of the distribution and storage facilities, transportation providers, and even manufacturers. In this paper a new model is developed for the design of sustainable supply chains with a focus on cities that captures the frequency of network link operations, which is especially relevant to cities due to frequent freight deliveries. Descriptive interviews were reviewed thoroughly with the conceptualization of the substantiated philosophy as a sociological technique of examination. All in all, this attempt of review established that the supply chain management method with its multidisciplinary foundations and assessments can benefit to overawed sectoral barriers in urban design.